Prevalence and Antibiotics Susceptibility Profile of Helicobacterpylori Isolated from Outdoor Patients Presenting Signs ofUlcerative Colitis in Three Hospitals in Niger State, Nigeria - Kuta, F.A.; Audu, S.L.; Garba, S.A.; Abdusalam, R.; Adabara, N.U. (Al-Hikmah Journal of Pure and Applied Sciences (AJPAS), 2016)
The present study was conducted to determine the prevalence and antibiotic susceptibility profile of Helicobacter pylori isolated from patients presenting signs of ulcerative colitis in three hospitals in Minna, Niger State, Nigeria. The study obtained a prevalence of 12%, out of the 350 patients screened for Helicobacter pylori, using Enzyme Linked Immunosorbent Assay (ELISA) technique. Patients with the highest rate of infection (3.43%) were within the age range 26-30years and the lowest prevalence of 0.29% was recorded among patients within the age range 1-5 years. Male patients recorded more prevalence (7.71%) compared to their female counterparts (4.29%). Patients from rural areas had more infection rate (10%) than patients from urban areas (2%). Patients that use water from streams recorded more infection rate (6%) compared to those that use water from the well (4%). The prevalence was more in Minna (5.43%), followed by Paiko (3.71%) and lastly Kuta (2.86%). H. Pylori was isolated from the gastric duodenal biopsies, using blood agar. Further identification of the isolates was through biochemical tests. Antibiotics susceptibility pattern indicated that all the antibiotics used were active against the H. pylori at high concentration but the organism demonstrated resistance on almost all the drugs used at low concentrations. Extensive awareness on H. Pylori infection among rural dwellers should be encouraged.